Business Tax Provisions of the 1962 and 1964 Acts: Discussion - Keith, E. Gordon (Journal of Finance, 1965)
E. Gordon Keith, Business Tax Provisions of the 1962 and 1964 Acts: Discussion, The Journal of Finance, Vol. 20, No. 2, Papers and Proceedings of the Twenty-Third Annual Meeting of the American Finance Association, Chicago, Illinois, December 28-30, 1964 (May, 1965), pp. 295-297